Closer to home - Lackey, Mercedes (Lackey, Mercedes. Herald spy, 2014)
Trained as a spy by the King's Own Herald, an orphan named Mags rises through the ranks of the Heralds' Collegium and uses his powerful Mindspeech gift to outmaneuver a royal court plot that risks his mentor and family.